Упростите выражение выражение: 1. (sina+cosa)^2+(sina-cosa)^2 -2 2. (sinx+1/sinx)^2+(cosx+1/cosx)^2 -tg^2x-ctg^2x 3. (sin^2a-tg^2a)/(cos^2a-ctg^2a) Заранее спасибо :3

Упростите выражение выражение: 1. (sina+cosa)^2+(sina-cosa)^2 -2 2. (sinx+1/sinx)^2+(cosx+1/cosx)^2 -tg^2x-ctg^2x 3. (sin^2a-tg^2a)/(cos^2a-ctg^2a) Заранее спасибо :3
Гость
Ответ(ы) на вопрос:
Гость
1. (sina+cosa)^2+(sina-cosa)^2 -2= =sin²x+2sinxcosx+cos²x+sin²x-2sinxcosx+cos²x-2=2-2=0 2. (sinx+1/sinx)^2+(cosx+1/cosx)^2 -tg^2x-ctg^2x= =sin²x+2+1/sin²x+cos²x+2+1/cos²x-tg²x-ctg²x= =1/sin²x+1/cos²x+5-tg²x-ctg²x=1+ctg²x+1+tg²x+5-tg²x-ctg²x=7 3. (sin^2a-tg^2a)/(cos^2a-ctg^2a)=(sin²a-sin²a/cos²a)/(cos²a-cos²a/sin²a)= =sin²a(cos²a-1)/cos²a :cos²a(sin²a-1)/sin²a=-sin^4a/cos²a*(-sin²a/cos^4a)= =sin^6a/cos^6a=tg^6a
Не нашли ответ?
Ответить на вопрос
Похожие вопросы